POLITICAL AND PERSONAL DISPLACEMENT IN THE LOWLAND - Jaiswal, Ankit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Amidst the vast corpus of diaspora literature present today, Jhumpa Lahiri’s narratives of the diasporic experience stand out remarkably from the others. Her novels not only highlight the classic diasporic issues of hybridity, alienation, and in betweenness, her novels make the reader question the very making of the diasporic experience. Her writing, I argue, is an immigrant’s way of trying to trace back to her roots, trying to connect with her homeland, or at least pay homage to what would have been her homeland. In this paper, I shall try to look at displacement, both geographical and emotional, and probe into the notion of otherness that is frequently experienced by individuals inhabiting liminal cultural spaces.